A RAG-based LLM Approach for Data Validation and Harmonization in Ship Design - Bronson, Janica; Teimouri, Maryam; Gaspar, Henrique; Fonseca, Icaro; Bierkowska, Karolina; Ginter, Filip; Koelman, Herbert (Switzerland, 2026)
Validating ship design data across systems is challenging due to fragmented information from multiple
sources, file types, and formats – from 2D drawings, 3D models, and specifications, often found in
unstructured text files. While unified 3D models aim to serve as a single source of truth, ensuring
accuracy and consistency across all representations remains a complex task. This paper presents a
retrieval-augmented generation (RAG) solution for extracting and comparing design parameters from
diverse files and formats. The approach aims to detect inconsistencies between documents and versions,
helping designers maintain data integrity and reduce manual effort throughout the ship design process.
23rd Conference on Computer and IT Applications in the Maritime Industries: COMPIT’25